Association of intrinsic capacity with functional ability, sarcopenia and systemic inflammation in pre-frail older adults - Merchant, Reshma Aziz; Chan, Yiong Huak; Anbarasan, Denishkrshna; Vellas, Bruno (Frontiers in Medicine, 2024)
Background Decline in intrinsic capacity (IC) has been shown to accelerate progression to disability. The study aims to explore association of IC composite score with functional ability, sarcopenia and systemic inflammation in pre-frail older adults. Methods Cross-sectional study of pre-frail older adults ≥60 years old recruited from the community and primary care centers. Composite scores of four domains of IC were measured: locomotion, vitality, cognition and psychological. FRAIL scale was used to define pre-frailty. Muscle mass was measured using the bioelectrical impedance analysis. Systemic inflammation biomarkers [Interleukin-6 (IL-6), Interleukin-10 (IL-10), Tumor Necrosis Factor Alpha (TNF-α), and Growth differentiated factor 15 (GDF-15)] were measured. Participants in the lowest tertile (T1) exhibited greater decline in IC. Results A total of 398 pre-frail older adults were recruited, mean age was 72.7 ± 5.8 years, 60.1% female, education level 7.8 years, and 85.2% were of Chinese ethnicity. A total of 75.1% had decline in locomotion, 40.5% in vitality, 53.2% in cognition and 41.7% in psychological domain. A total of 95% had decline in at least one domain. T1 was significantly associated with ADL impairment (aOR 3.36, 95% CI 1.78–6.32), IADL impairment (aOR 2.37, 95% CI 1.36–4.13), poor perceived health (aOR 0.96, 95% CI 0.95–0.98), fall (aOR 1.63, 95% CI 1.05–2.84), cognitive impairment (aOR 8.21, 95% CI 4.69–14.39), depression (aOR 101.82, 95% CI 33.62–308.37), and sarcopenia (aOR 2.40, 95% CI 1.60–5.45). T1 had significant associations with GDF-15, IL-10, and IL-10 to TNF-α ratio. Conclusion Decline in IC composite score among pre-frail older adults was associated with functional limitation, sarcopenia, and systemic inflammation.